Randomized Controlled Trial of Enhanced Recovery Program Dedicated to Elderly Patients After Colorectal Surgery. Issue 9 (September 2019) - Ostermann, Sandrine; Morel, Philippe; Chalé, Jean-Jacques; Bucher, Pascal; Konrad, Béatrice; Meier, Raphaël P. H.; Ris, Frederic; Schiffer, Eduardo R. C.
Abstract : BACKGROUND: Enhanced recovery program is a multimodal, multidisciplinary-team, evidence-based care approach to reduce perioperative surgical stress, decrease morbidity and hospital stay, and improve recovery after surgery. This program may be most beneficial for elderly (≥70 y), but sparse series have investigated this question. OBJECTIVE: Feasibility and efficiency of a dedicated enhanced recovery program in the elderly as compared with standard care were studied. DESIGN: This was a nonblinded, randomized controlled study. SETTINGS: This study was conducted in a single high-volume university hospital. PATIENTS: A total of 150 eligible elderly patients undergoing elective colorectal surgery were included. INTERVENTIONS: Enhanced recovery after colorectal elective surgery in elderly patients was studied. MAIN OUTCOME MEASURES: The primary outcome was 30-day postoperative morbidity. Additional outcomes included hospital stay, readmission, postoperative pain, opioid consumption, independence preservation, and protocol compliance. RESULTS: An enhanced recovery program reduces postoperative morbidity according to Clavien-Dindo classification by 47% as compared with standard care (35% vs 65%; p = 0.0003), total number of complications (54 vs 118; p = 0.0003), and infectious complications (13 vs 29; p = 0.001). No anastomotic leak was recorded in the enhanced recovery group versus 5 for the standard group ( p = 0.01). The enhanced recovery program resulted in shorter hospital stay (7 vs 12 d; p = 0.003) and better independence preservation (home discharge, 87% vs 67%; p = 0.005). A high protocol compliance of 77.2% could be achieved in this population. According to multivariate analysis, enhanced recovery program was strongly associated with reduced morbidity (OR = 0.23 (95% CI, 0.09–0.57); p = 0.001), less severe complications (OR = 0.36 (95% CI, 0.15–0.84); p = 0.02), and shorter hospital stay (OR = 2.07 (95% CI, 1.33–3.22); p = 0.001). LIMITATIONS: Limitations were a single-center recruitment and the impossibility of subject or healthcare professional blinding attributed to the nature of this multimodal program. CONCLUSIONS: Enhanced recovery program is safe and improves postoperative recovery in elderly patients with decreased morbidity, shorter hospital stay, and better maintenance of independence. It should therefore be considered as a standard of care for elective colorectal surgery in elderly patients. See Video Abstract at http://links.lww.com/DCR/A981 . TRIAL REGISTRATION: clinicaltrials.gov identifier: NCT01646190. ENSAYO CONTROLADO ALEATORIZADO DE UN PROGRAMA DE RECUPERACIÓN INTENSIFICADA DEDICADO A PACIENTES DE EDAD AVANZADA DESPUÉS DE CIRUGÍA COLORECTAL: ANTECEDENTES: El Programa de Recuperación Intensificada es un enfoque de atención multimodal, multidisciplinaria y basada en evidencia para reducir el estrés quirúrgico perioperatorio, disminuir la morbilidad y la estancia hospitalaria, y mejorar la recuperación después de la cirugía. Este programa puede ser más beneficioso para las personas mayores (≥70 años), pero pocas series han investigado esta pregunta. OBJETIVO: Viabilidad y eficiencia del Programa de Recuperación Intensificada dedicado en personas de edad avanzada en comparación con la atención estándar. DISEÑO: Este fue un estudio controlado, aleatorizado, sin método ciego. ESCENARIO: Este estudio se realizó en un único hospital universitario de alto volumen. PACIENTES: Un total de 150 pacientes de edad avanzada elegibles sometidos a cirugía colorrectal electiva fueron incluidos. INTERVENCIONES: Recuperación Intensificada después de cirugía electiva colorrectal en pacientes de edad avanzada. PRINCIPALES MEDIDAS DE RESULTADO: El resultado primario fue la morbilidad postoperatoria a 30 días. Los resultados adicionales incluyeron estancia hospitalaria, reingreso, dolor postoperatorio, consumo de opioides, preservación de la independencia y cumplimiento del protocolo. RESULTADOS: El Programa de Recuperación Intensificada reduce la morbilidad postoperatoria según la clasificación de Clavien-Dindo en un 47% en comparación con la atención estándar (35% vs 65%; p = 0.0003), número total de complicaciones (54 vs 118; p = 0.0003) y complicaciones infecciosas (13 vs 29; p = 0.001). No se registró ninguna fuga anastomótica en el grupo de Recuperación Intensificada frente a 5 para el grupo estándar ( p = 0.01). El Programa de Recuperación Intensificada dio como resultado una estancia hospitalaria más corta (7 contra 12 días; p = 0.003) y una mejor conservación de la independencia (alta hospitalaria: 87% vs 67%; p = 0.005). Se pudo lograr un alto cumplimiento del protocolo del 77.2% en esta población. De acuerdo con el análisis multivariable, el Programa de Recuperación Intensificada se asoció fuertemente con la reducción de morbilidad (OR = 0.23; IC 95%: 0.09–0.57; p = 0.001), menos complicaciones graves (OR = 0.36; IC 95%: 0.15–0.84; p = 0.02) y estancia hospitalaria más corta (OR = 2.07; IC 95%: 1.33–3.22; p = 0.001). LIMITACIONES: Las limitaciones fueron un centro único de reclutamiento y la imposibilidad de que los pacientes o el profesional de la salud tuvieran cegamiento debido a la naturaleza de este programa multimodal. CONCLUSIONES: El Programa de recuperación Intensificada es seguro y mejora la recuperación postoperatoria en pacientes de edad avanzada, con menor morbilidad, menor estancia hospitalaria y mejor mantenimiento de la independencia. Por lo tanto, debe considerarse como un estándar de atención para la cirugía colorrectal electiva en pacientes de edad avanzada. Vea el Resumen en video en http://links.lww.com/DCR/A981 .